M23 COPD exacerbations of longer duration worsens health related quality of life. (14th November 2013) - Donaldson, GC; MacKay, AJ; Singh, R; Allinson, J; Brill, S; Wedzicha, JA
Abstract : Introduction: Patient's quality of life is related to the frequency of COPD exacerbations [Seemungal et al AJRCCM 1998: 157: 1418–1422]. There is increasing interest in reducing the duration of exacerbations but little evidence that this benefits patient's quality of life. Methods: We analysed data from 384 patients in the London COPD cohort collected between 1995 and 2012. Patients completed diary cards recording respiratory symptoms. Exacerbation onset was defined as the first of two days of 2 major symptoms (increased breathlessness, sputum volume or purulence) or 1 major and 1 minor symptom (cold, increased cough, increased wheeze, sore throat). Recovery was defined as the first of two symptom free days and exacerbation duration was defined as the period between onset and recovery.. Patients completed the St. George's Respiratory Questionnaire (SGRQ) annually when clinically stable. To avoid bias with repeated measures, exacerbation recovery and SGRQ total scores were averaged. FEV1 % predicted was measured at recruitment. Results: The 384 COPD patients (246 male); mean age 68.6 years (SD8.4), FEV1 % predicted 45.8% (16.6) and FEV1 /FVC 45.8% (12.2) with 122 patients (32.1%) still smoking at recruitment. There were 3498 exacerbations (median annual rate = 2.13 (IQR 1.0–3.2)). The median exacerbation duration was 10 days (IQR 6–18). Exacerbation duration was not available for 350 (10.0%) exacerbations as no symptoms were recorded and for a further 109 (3.1%) where the patient continued to recorded symptoms post-exacerbation for 100 days or more. In a multiple linear regression model, total SGRQ score increased by 0.20 units/1 day increase in exacerbation duration (95% CI 0.008–0.39; p = 0.041) after allowance for FEV1 % predicted and exacerbation frequency. The results suggest that halving the duration of 4 exacerbation events from 10 to 5 days will produce a 4 unit change in the total SGRQ score. Concluison: Shorter exacerbations are associated will improved quality of life. More research is needed on acute interventions designed to ameliorate exacerbations.